China's dream the culture of Chinese communism and the secret sources of its power - Brown, Kerry 1967- (Cambridge, UK Medford, MA Polity, 2018)
"China's Dream is the first book to explore the Communist Party as a cultural, rather than a political, entity. Kerry Brown takes us on a fascinating journey through the least understood aspect of China today - not the economic revolution in the material world, but the deep cultural revolution already underway in Chinese people's daily lives"--
"The Communist Party of China is one of the great political forces of modern times. In charge of the destiny of a fifth of humanity, it survives despite the collapse of similar systems elsewhere. Few however understand the sources of this resilience, or, for that matter, what the Party itself stands for is the first book to explore the Communist Party as a cultural, rather than a political, entity. It looks at the narratives the Party has created to recount its own history, with the moral story about national rejuvenation and renaissance that these encode. It does not shy away from the thorny issue of how a Party under Mao Zedong, one associated with self-sacrifice, collectivist effort and anti-individualism, came to pragmatically embrace market capitalism and a new ethics. Here self-development and the space we now call Deep China, the China of individual Chinese people's lives outside the bounds of politics, sit beside the maintenance of state and party control over key areas of public life. The tensions to which this gives rise have resulted in a crisis of values, which is now being addressed - with very mixed results - by the CCP. Drawing on his extensive knowledge of contemporary China, Kerry Brown takes us on a unique and fascinating journey through the least understood aspect of China today - not the great economic revolution in the material world, but the deep cultural revolution already underway in Chinese people's daily lives"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Zhongguo gong chan dang; Social change -- China; Communism -- Social aspects -- China; POLITICAL SCIENCE / Globalization; China -- Social policy; China -- Social conditions -- 2000-.